2015
DOI: 10.5455/medarh.2015.69.103-106
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of B and E Vitamins with Diclofenac in Reducing Pain Due to Osteoarthritis of the Knee

Abstract: Background:Knee osteoarthritis is one of the most prevalent chronic disorders. Several pharmacological and non pharmacological approaches are used to treat this disease. Today, the effect of B and E vitamins on rheumatology diseases is being discussed. In this study, the efficacy of B and E vitamins accompanied with diclofenac on pain relief in patients with knee osteoarthritis was investigated and compared.Methods:In this double-blinded clinical trial, 120 patients with knee osteoarthritis referring training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
5
0
9
Order By: Relevance
“…The study suggests that vitamins K, B, and C may have a protective role against knee OA and might lead to disease-modifying treatments, in part via the Krebs cycle. A clinical trial showed that vitamin B complex including thiamine, niacin, and cobalamin significantly reduced knee pain in knee OA patients and the decrease in knee pain was significantly higher in the patients taking vitamin B complex than those in the vitamin E and diclofenac (COX-2 inhibitor) groups [31]. While B vitamins, such as thiamine, riboflavin, and niacin, are important for the Krebs cycle for energy production, their pain reduction effect observed in this clinical trial might be also via other pathways, such as anti-inflammatory pathways or an enhanced effect and/or availability of norepinephrine, as proposed by the authors [31].…”
Section: Energy Metabolic Pathwaysmentioning
confidence: 99%
“…The study suggests that vitamins K, B, and C may have a protective role against knee OA and might lead to disease-modifying treatments, in part via the Krebs cycle. A clinical trial showed that vitamin B complex including thiamine, niacin, and cobalamin significantly reduced knee pain in knee OA patients and the decrease in knee pain was significantly higher in the patients taking vitamin B complex than those in the vitamin E and diclofenac (COX-2 inhibitor) groups [31]. While B vitamins, such as thiamine, riboflavin, and niacin, are important for the Krebs cycle for energy production, their pain reduction effect observed in this clinical trial might be also via other pathways, such as anti-inflammatory pathways or an enhanced effect and/or availability of norepinephrine, as proposed by the authors [31].…”
Section: Energy Metabolic Pathwaysmentioning
confidence: 99%
“…Diclofenac, which belongs to the nonsteroidal anti-inflammatory drugs, is probably the most commonly used pain reliever ( 32 ). As an anti-inflammatory and analgesic drug, it is probably the most efficient inhibitor of prostaglandins, which are used for treatment of rheumatic diseases ( 33 ) and post-operational pain relievers ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…An intramuscular injection of diclofenac + B vitamin mixture showed a superior analgesic effect compared with the injection of diclofenac alone (Magaña- Villa et al, 2013). A human experiment of patients with knee OA indicated stronger analgesic property of vitamin B than vitamin E and diclofenac; the study highlighted the potential effects of vitamin B on TMD (Dehghan, 2015). Mechanically, the anti-inflammatory and analgesic effect may relate to the cyclooxygenase pathway and opioid receptors (Tamaddonfard et al, 2018).…”
Section: Orally Administrated Agents Vitamin B Complexmentioning
confidence: 99%